2023
DOI: 10.1007/s00415-022-11547-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light (NfL) as biomarker in serum and CSF in status epilepticus

Abstract: Objective We explored the potential of neurofilament light chain (NfL) in serum and cerebrospinal fluid as a biomarker for neurodestruction in status epilepticus. Methods In a retrospective analysis, we measured NfL in serum and cerebrospinal fluid samples of patients with status epilepticus using a highly sensitive single-molecule array technique (Simoa). Status epilepticus was diagnosed according to ILAE criteria. Additionally, we employed an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…These findings were recently replicated by a German group [65]. Their study also showed significantly elevated sNfL levels in patients with SE compared to healthy controls.…”
Section: Neurofilamentsmentioning
confidence: 57%
See 1 more Smart Citation
“…These findings were recently replicated by a German group [65]. Their study also showed significantly elevated sNfL levels in patients with SE compared to healthy controls.…”
Section: Neurofilamentsmentioning
confidence: 57%
“…An important advantage of NfL is its reliability in measurement in serum/blood. Additionally, two studies on humans [63,65] and a preclinical study [60] have demonstrated a close and optimal correlation between the peripheral and central compartments.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, a clinical need exists for readily available and non‐invasive serum biomarkers that could assist with discrimination of genetic vs structural causes of epilepsy or identification of epileptic patients that recently have experienced seizures. Serum NfL concentrations are increased in humans experiencing status epilepticus compared to both healthy people and those with epilepsy who experience occasional isolated seizures 9,10 . Furthermore, serum NfL concentrations in humans correlate well with CSF concentrations in numerous neurological diseases, and thus serum NfL concentrations generally are considered reliable biomarkers for CNS disease 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Serum NfL concentrations are increased in humans experiencing status epilepticus compared to both healthy people and those with epilepsy who experience occasional isolated seizures 9,10 . Furthermore, serum NfL concentrations in humans correlate well with CSF concentrations in numerous neurological diseases, and thus serum NfL concentrations generally are considered reliable biomarkers for CNS disease 10,11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation